IoT fire detector with Telegram notification - Saputra, Agusriyanda; Aswardi, Aswardi (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Fire is a disaster whose arrival cannot be predicted or can occur at anytime and anywhere. The impact is in the form of material loss and loss of life, therefore, there is a need for early detection and early prevention of fire. Technological advances that can be used in early detection efforts are the Internet of Things (IoT). IoT can connect electronic devices that can connect via the internet so that they can quickly provide data and information. Fire incidents can occur in public places or in residential areas. Therefore, a tool was created which aims to be able to design and monitor a fire extinguishing system using telegram via NRF24L01, phototransistor sensor and MQ2 smoke sensor with relay driver output and DC pump via Arduino as well as LCD, buzzer and ESP2866. The fire extinguishing system method uses telegram via NRF24L01, phototransistor sensor and MQ2 smoke sensor with relay driver output and DC pump via Arduino. As well as LCD, buzzer and ESP2866 activated via Wi-Fi using condition output from the phototransistor sensor and MQ2 smoke sensor via NRF24L01 in the form of real-time data which is active and if the NRF24L01 receives data it will activate the relay driver to turn on and off the dc pump and buzzer, after which the data is sent to the Telegram application. After testing and analyzing the fire extinguishing system, it can be concluded that the fire extinguishing system has been able to work properly.